Key Outcomes of Approbation and Implementation of Professional Standard for Teachers - Zabrodin Yu.M; Sergomanov P.A (Moscow State University of Psychology and Education, 2016)
We describe the concept of the professional standard for teachers - educators, methodological approaches to the description of the teacher professional activities, teacher on a background of a brief history of the formation and development of the development and application of professional standards in our country and abroad. We describe the structure, functions and content of the teacher professional standard. We discuss the problems of testing and use of the professional teacher standards, prospects and main directions of its application in the upgrading of teacher education.